A Markerless Method for Genome Engineering in Zymomonas mobilis ZM4 - Lal, Piyush Behari; Wells, Fritz M.; Lyu, Yucai; Ghosh, Indro N.; Landick, Robert; Kiley, Patricia J. (Frontiers in Microbiology, 2019)
Metabolic engineering of the biofuel-producing Zymononas mobilis is necessary if we are to unlock the metabolic potential present in this non-model microbe. Manipulation of such organisms can be challenging because of the limited genetic tools for iterative genome modification. Here, we have developed an efficient method for generating markerless genomic deletions or additions in Z. mobilis. This is a two-step process that involves homologous recombination of an engineered suicide plasmid bearing Z. mobilis targeting sequences and a subsequent recombination event that leads to loss of the target gene and suicide plasmid. A key feature of this strategy is that GFP expressed from the suicide plasmid allows easy identification of cells that have lost the plasmid by using a fluorescence activated cell sorter. Using this method, we demonstrated deletion of the gene encoding lactate dehydrogenase (ldh) and the operon for cellulose synthase (bcsABC). In addition, by modifying the plasmid design, we demonstrated targeted insertion of the crtIBE operon encoding a neurosporene biosynthetic pathway into the Z. mobilis genome without addition of any antibiotic resistance genes. We propose this approach will provide an efficient and flexible platform for improved genetic engineering of Z. mobilis.